Nonlinear Two-Parameter Spectral Problems in Studies of Solutions of Differential and Nonlinear Integral Equations of Hammerstein Type - Savenko, Petro (Proceedings of the ... International Seminar/Workshop on Direct and Inverse Problems of Electromagnetic and Acoustic Wave Theory, 2019)
The theory and methods of solving the nonlinear multi-parametric spectral problems and their application in investigations of spectral properties of linear differential equations, which comprise the spectral parameters in equation coefficients and boundary conditions nonlinearly, are considered. Investigation of the problem of non-uniqueness of solutions to the non-linear integral equations of the Hammerstein type, which are used in the theory of the synthesis of antennas with a plane radiating aperture, is presented. A number of numerical examples of solving specific spectral problems are given.